Surgical treatment of bilateral fracture of atrophic mandibula: Case report (Research, Society and Development, 2021)
Mandibular atrophy occurs due to several factors such as periodontitis, periapical lesions, early tooth loss, use of poorly adapted prostheses that promote bone resorption over time. This condition provides fragility to the remaining bone structure and susceptibility to fractures. Atrophic mandible fractures represent a challenge to the Oral and Maxillofacial Surgeon due to several peculiarities in the management of treatment and oral rehabilitation. The treatment of choice for patients with atrophic mandible fracture is surgery, which aims to reduce and immobilize the fracture segments, in order to restore aesthetics and function. In this way, an individualized assessment must be carried out in search of the best biomechanics of the osteosynthesis material to be used, as adequate stability can be achieved through several fixation methods. The objective of this work is to report a clinical case of a male patient, victim of an accident with a large animal evolving with bilateral fracture of the atrophic mandible body. We opted for surgical treatment of the fracture with simplification of the fracture bone stumps using miniplates and subsequent installation of the load-bearing system plate, evolving in the postoperative period without complications.